2019
DOI: 10.1002/jcp.28847
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic storage of erythrocytes slows down storage lesions and prolongs shelf‐life

Abstract: Conventional storage conditions of erythrocytes cause storage lesions. We propose that hypoxic storage conditions, involving removal of oxygen and replacement with helium, the changes in stored erythrocytes under hypoxic condition were observed and assessed. Erythrocytes were divided into two equal parts, then stored in conventional and hypoxic conditions, separately. Blood gas analysis, hemorheology, and hemolysis were performed once a week. Energy metabolism and membrane damage were monitored by enzyme-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…In contrast, a study on erythrocyte storage demonstrated that hypoxic storage inversely maintained erythrocyte stability, with no significant alterations in erythrocyte deformation and aggregation compared to normal storage conditions. 77 …”
Section: Hypoxia Affects Erythrocyte Membrane Propertiesmentioning
confidence: 99%
“…In contrast, a study on erythrocyte storage demonstrated that hypoxic storage inversely maintained erythrocyte stability, with no significant alterations in erythrocyte deformation and aggregation compared to normal storage conditions. 77 …”
Section: Hypoxia Affects Erythrocyte Membrane Propertiesmentioning
confidence: 99%